THE EFFECT OF COGNITIVE RESTRUCTURING INTERVENTION ON TOBACCO SMOKING AMONG ADOLESCENTS IN SENIOR SECONDARY SCHOOL IN ZARIA KADUNA STATE, NIGERIA - Umaru, Yunusa; M. I., Abdullahi; O., Oliagba; Sambo, Sani; Abdulwahid, Umma (European Scientific Journal, ESJ, 2014)
This study employs a quasi-experiment, non-equivalent control group, pretest-posttest design in investigating the effect of Cognitive Restructuring Intervention Program on tobacco smoking among adolescents in senior secondary school in Zaria Educational Zone of Kaduna State, Nigeria. The sample was 129 (71 male and 58 females) schooling Adolescents drawn from four schools in Zaria Educational zone. An instruction tagged cognitive behaviours intervention scale (CBIS) was adopted and used for the study. Data were analyzed using means t-test and analysis of covariance (ANCOVA). Findings indicate that cognitive restructuring intervention program (CRIP) significantly affects tobacco usecessation. Recommendations are by made which include a call for psychologists/counselors to be employed in schools and taught how to use new skills in curtailing tobacco smoking among students.